Developing entrepreneurship between the Autonomous University of Yucatán and the Technological Institute of Costa Rica - Chaves-Abarca, Randall (2017)
The academic exchange of students and teachers is a valuable option for contributing to professional and personal growth of the participants. In turn, this effort to share innovative ideas among students can enhance entrepreneurship. This has been the conviction of a group of academics from the Autonomous University of Yucatán and the Technological Institute of Costa Rica that have been collaborating and making exchanges between both institutions for more than ten years. The exigency in the educational process carried out has allowed to generate proposals by identifying opportunities and having a rigorous project structuration. Thereby there is a contribution to help the student learning process, being the students with the winning projects of competitions in each country who are given the opportunity to travel and know another culture.For many participants, this experience impacted positively on aspects such as security and self confidence, besides being one of the first options to share with people from another country and even to go abroad for the first time. Significantly good understanding in the relations among academics and perseverance to generate proposals that have justified these exchanges made for many years. This article shares this experience from its beginings. It presents methodological aspects, main projects and culminates with an evaluation made by Costa Rican students who traveled to Mexico and some data related to their current professional activities.